Marginal chipping factor in machinable zirconia and lithium disilicate ceramic veneer restorations - Hasan, Nadia H; Malallah, Ali; Hazim, Mohammed (International Journal of Dental Materials, 2024)
Background: The marginal edges of the laminate veneer ceramic restorations are very critical areas that play a very determinant role in the success of this type of esthetic restorations.Aim: To evaluate the marginal chipping factor of laminate veneer restorations prepared from both zirconia lithium disilicate materials.Materials and methods: Two typodont teeth representing the upper central incisors were used to prepare laminate veneers with an overlapping incisal design. These veneers were fabricated in two thicknesses (0.5 mm and 0.3 mm) using three types of multilayer zirconia materials with varying yttria percentages (3Y, 5Y, and 3Y/5Y) as well as lithium disilicate computer-aided-design (CAD) blocks. The veneers were divided into four groups based on the yttria percentage and further subdivided into two subgroups for the thickness. Top-view images of the veneer margins were captured and imported into the Image Pro Plus software. The average periphery of each veneer margin was 30 mm. The lengths of the chipped margins were measured under a stereomicroscope, and the CF was calculated.Results: One-way ANOVA suggested significant differences among the ceramics. e.max CAD ceramic veneers exhibited the highest mean CF values (4.72, 5.9), whereas 3Y/5Y zirconia veneers demonstrated the lowest mean CF values (0.74, 1.54) for 0.5 mm and 0.3 mm thicknesses, respectively. Independent t-tests indicated no significant difference in the CF between 0.5 mm and 0.3 mm thicknesses for each ceramic material.Conclusion: Different ceramic materials exhibited varying levels of marginal chipping, with zirconia ceramics demonstrating lower CF than lithium disilicate ceramics. Reducing the veneer thickness from 0.5 mm to 0.3 mm did not significantly affect the CF.